Tenascin-C: Friend or Foe in Lung Aging? - Gremlich, Sandrine; Cremona, Tiziana P.; Yao, Eveline; Chabenet, Farah; Fytianos, Kleanthis; Roth-Kleiner, Matthias; Schittny, Johannes C. (Frontiers in Physiology, 2021)
Lung aging is characterized by lung function impairment, ECM remodeling and airspace enlargement. Tenascin-C (TNC) is a large extracellular matrix (ECM) protein with paracrine and autocrine regulatory functions on cell migration, proliferation and differentiation. This matricellular protein is highly expressed during organogenesis and morphogenetic events like injury repair, inflammation or cancer. We previously showed that TNC deficiency affected lung development and pulmonary function, but little is known about its role during pulmonary aging. In order to answer this question, we characterized lung structure and physiology in 18 months old TNC-deficient and wild-type (WT) mice. Mice were mechanically ventilated with a basal and high tidal volume (HTV) ventilation protocol for functional analyses. Additional animals were used for histological, stereological and molecular biological analyses. We observed that old TNC-deficient mice exhibited larger lung volume, parenchymal volume, total airspace volume and septal surface area than WT, but similar mean linear intercept. This was accompanied by an increase in proliferation, but not apoptosis or autophagy markers expression throughout the lung parenchyma. Senescent cells were observed in epithelial cells of the conducting airways and in alveolar macrophages, but equally in both genotypes. Total collagen content was doubled in TNC KO lungs. However, bBasal and HTV ventilation revealed similar respiratory physiological parameters in both genotypes. Smooth muscle actin (α-SMA) analysis showed a faint increase in α-SMA positive cells in TNC-deficient lungs, but a marked increase in non-proliferative α-SMA+desmin+ cells. Major TNC-related molecular pathways were not up- or down-regulated in TNC-deficient lungs as compared to WT; only minor changes in TLR4 and TGFβR3 mRNA expression were observed. In conclusion, TNC-deficient lungs at 18 months of age showed exaggerated features of the normal structural lung aging described to occur in mice between 12 and 18 months of age. Correlated to the increased pulmonary function parameters previously observed in young adult TNC-deficient lungs and described to occur in normal lung aging between 3 and 6 months of age, TNC might be an advantage in lung aging.